Non-performing loans at the dawn of IFRS 9: regulatory and accounting treatment of asset quality. Issue 1 (January 2018) - Bholat, David; Lastra, Rosa; Markose, Sheri; Miglionico, Andrea; Sen, Kallol
Abstract Asset quality is a key indicator of sound banking. However, it is difficult for banking regulators and investors to assess it in the absence of a common, cross-border scheme to classify assets. Currently, no standard is applied universally to categorise loans, the most sizeable asset on banks' balance sheets. As a corollary, definitions of non-performing loans (NPLs), despite recent steps towards greater harmonisation, continue to vary between jurisdictions. This paper offers a comprehensive analysis of NPLs and considers variations in the treatment of NPLs across countries, accounting regimes and firms. The paper relies on a multidisciplinary perspective and addresses legal, accounting, economic and strategic aspects of loan loss provisioning and NPLs. A harmonised approach to NPL recognition is particularly desirable, in view of the fact that IFRS 9, the new accounting standard on loan loss provisioning, will be mandatory from January 2018. IFRS 9 changes the relationship between NPLs and provisions, by relying on greater judgement to determine provisions. The potential for divergence makes the need for comparable indicators against which to assess asset quality all the greater.